Detection of Helicobacter pylori in patients with head and neck cancer: Results from a prospective comparative study combining serology, polymerase chain reaction, and rapid urease test. Issue 5 (20th June 2015) - Morand, Grégoire B.; Fellmann, Jonas; Laske, Roman D.; Weisert, Jan U.; Soltermann, Alex; Zbinden, Reinhard; Probst, Rudolf; Huber, Gerhard F.
Abstract: Background: The purpose of this study was to evaluate prospectively the presence and impact of the gastric carcinogen Helicobacter pylori ( H. pylori ) in the upper aerodigestive tract. Previous studies suggested it could represent a risk factor for head and neck squamous cell carcinoma (HNSCC). Methods: Serology, rapid urease test, and quantitative polymerase chain reaction (qPCR) for H. pylori were performed in patients with head and neck cancer ( N  = 56) and cancer‐free controls ( N  = 90). Comparison between groups was done using logistic regression analysis. Results: Rates of positive serology and rapid urease test did not differ between the 2 groups in logistic regression analysis ( p  = .677 and p  = .633, respectively). Birth in a developing country and age above 50 years old were predictors of positive serology ( p  < .001 and p  = .040, respectively). Using qPCR, no biopsy showed the presence of H. pylori . Conclusion: This study challenges the concept that H. pylori may be a risk factor for HNSCC. © 2015 Wiley Periodicals, Inc. Head Neck 38: 769–774, 2016